ANALISIS TINGKAT KEPUASAN WISATAWAN DOMESTIK TERHADAP PELAYANAN RESERVASI TIKET PESAWAT DI GARUDA INDONESIA DENPASAR, BALI - Godang, Mr.; Sendra, I Made; Indrawati, Yayu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 2 No 2 (2014): Jurnal IPTA (December 2014)DO - 10.24843/IPTA.2014.v02.i02.p03)
Bali, whose name is identical with tourism, is one of the tourist destination in Indonesia, whose name has been synonymous with tourism. Airlines, which one of them is Garuda Indonesia, became one of the factors that developed tourism in Bali. The background of this research due to complaints from tourists who made a reservation at Garuda Indonesia. The purpose of this study is to determine the satisfaction of domestic touristto ticket reservation service at Garuda Indonesia, so we can know which variables that must be maintained and enhanced. This research was conducted using the method of Importance-Performance Analysis by distributing questionnaires to 60 respondents domestic tourist who make ticket reservations at Garuda Indonesia which service dimensions studied are reliability, responsiveness, assurance, empathy, and tangible. Based on the research that has been done, it could be concluded that the overall rating is not satisfied with the service provided by the staff of Garuda Indonesia, both in terms of reliability, responsiveness, assurance, empathy, and tangible so that the performance needs to be improved.Garuda Indonesia can improve and enhance the service quality of staff and domestic tourists satisfaction by looking the sequence of priority in airline ticket reservation service indicator.
Keywords: Service Quality